2007
DOI: 10.1088/0953-8984/19/36/365239
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering studies on multiferroic YMnO3

Abstract: YMnO(3) is a multiferroic material in which ferroelectric and antiferromagnetic ordering can coexist. We have studied a YMnO(3) bulk crystal in detail by Raman scattering in a wide temperature range of 15-1200 K, with comparison to a previous experiment at room temperature and a theoretical prediction for Raman-active phonon modes. In the low-temperature ferroelectric phase, the observed phonon spectra showed anomalous temperature variation at the Néel temperature, T(N)∼80 K, suggesting a coupling between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
55
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 14 publications
18
55
0
Order By: Relevance
“…The most intense and sharp spectral feature in the parallel configuration is the peak at 680 cm −1 . Comparing with the previous results, [9,14] this peak can be assigned to the A 1 phonon. The broad peak at 1280 cm −1 can be assigned as the second harmonic of the A 1 phonon.…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…The most intense and sharp spectral feature in the parallel configuration is the peak at 680 cm −1 . Comparing with the previous results, [9,14] this peak can be assigned to the A 1 phonon. The broad peak at 1280 cm −1 can be assigned as the second harmonic of the A 1 phonon.…”
Section: Methodssupporting
confidence: 80%
“…In addition, several weak peaks are observed in the parallel configuration, which can be assigned on the basis of previous research. [9,14] In the crossed configuration, the peak at 680 cm −1 is also observed with much weaker intensity, which is not allowed by the Raman selection rule. We expect that this is mainly related to disorder and departures from exact selection rules in resonant Raman scattering.…”
Section: Methodsmentioning
confidence: 93%
“…The study of magnetic and lattice excitations using inelastic neutron scattering experiments provided evidence for a strong coupling between magnons and phonons which appear to hybridize in one mixed elementary excitation [154], similar to the electromagnons studied in multiferroic orthorhombic manganites [161,162]. Raman and infrared absorption investigations of the temperature dependent phonon spectrum of YMnO 3 and LuMnO 3 have found a kink at and an abnormal hardening in the magnetically ordered phase, indicating strong spinphonon coupling [163][164][165]. Similar phonon hardening was also found in compounds with rare earth magnetic moments, HoMnO 3 and ErMnO 3 [128,166].…”
Section: +mentioning
confidence: 58%
“…The in-plane bonding force constants would be closely related with the lattice constant a, and the inter-plane bonding force constants with the lattice constant c. Therefore, our results suggest that, in hexagonal RMnO 3 thin films, both the lattice constants a and c would show a systematic variation with R, and the lattice constant c would have a weaker R dependence. The phonon scattering in hexagonal RMnO 3 has been investigated for various R ions, R = Y, [25,26] R = Ho, [27] R = Er, [28] R = Yb, [29] and R = Lu. [30] Comparing the phonon peak positions in these reported studies, we noticed that almost all the observed phonons did not show any systematic variation with R, contrary to our experimental findings.…”
Section: Resultsmentioning
confidence: 99%